2013
DOI: 10.1126/science.1243759
|View full text |Cite
|
Sign up to set email alerts
|

Selective C-H Fluorination of Pyridines and Diazines Inspired by a Classic Amination Reaction

Abstract: Fluorinated heterocycles are prevalent in pharmaceuticals, agrochemicals, and materials. However, reactions that incorporate fluorine into heteroarenes are limited in scope and can be hazardous. We present a broadly applicable and safe method for the site-selective fluorination of a single carbon-hydrogen bond in pyridines and diazines using commercially available silver(II) fluoride. The reactions occur at ambient temperature within 1 hour with exclusive selectivity for fluorination adjacent to nitrogen. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
144
1
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(157 citation statements)
references
References 49 publications
2
144
1
5
Order By: Relevance
“…70) [119,120,123,[133][134][135][136][137][138]176]. The reaction proceeds at room temperature in 1 h and affords 2-fluoropyridines with high selectivity.…”
Section: Reactions Proposed To Proceed Via One-electron Pathwaysmentioning
confidence: 99%
“…70) [119,120,123,[133][134][135][136][137][138]176]. The reaction proceeds at room temperature in 1 h and affords 2-fluoropyridines with high selectivity.…”
Section: Reactions Proposed To Proceed Via One-electron Pathwaysmentioning
confidence: 99%
“…. [13] The reactions of pyridines, quinolines, and various diazines afford the monofluorination products in good yields with exclusive ortho-position selectivity. This is a useful synthetic approach for the late-stage modification of complex molecules containing heterocycles such as pyridines.…”
Section: Introductionmentioning
confidence: 99%
“…The authors 57 proposed a mechanism that involves initial coordination of AgF 2 to pyridine, followed by addition of the [Ag]-F bond across the π system of the pyridine to form an amidosilver(II)-fluoride complex58 (Scheme 12). The authors also observed a KIE of 2.9, suggesting that the coordination of pyridine to AgF 2 and the addition step are reversible.…”
mentioning
confidence: 99%